2012
DOI: 10.1002/lary.23786
|View full text |Cite
|
Sign up to set email alerts
|

Periostin may play a protective role in the development of eosinophilic chronic rhinosinusitis with nasal polyps in a mouse model

Abstract: The loss of periostin appears to enhance polyplike lesion formation and mast cell infiltration in a mouse model of eosinophilic rhinosinusitis with nasal polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
(63 reference statements)
1
28
0
Order By: Relevance
“…Similarly, many investigators have utilized the NP mouse model using OVA and SEB to show the effects of their candidate drugs or target molecules. Kim et al showed that loss of periostin appeared to enhance polyp‐like lesion formation and mast cell infiltration in a mouse model of eosinophilic rhinosinusitis with NPs . They induced the NP formation in both periostin‐null and wild‐type mice by the repeated nasal administration of OVA and SEB.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many investigators have utilized the NP mouse model using OVA and SEB to show the effects of their candidate drugs or target molecules. Kim et al showed that loss of periostin appeared to enhance polyp‐like lesion formation and mast cell infiltration in a mouse model of eosinophilic rhinosinusitis with NPs . They induced the NP formation in both periostin‐null and wild‐type mice by the repeated nasal administration of OVA and SEB.…”
Section: Discussionmentioning
confidence: 99%
“…The primary application of using the allergic model of sinonasal inflammation is testing of novel topical or systemic drugs to reverse inflammation . In order to determine the most sensitive and reliable measure of drug efficacy, we pilot‐tested a common topical anti‐inflammatory drug used in treating CRS, budesonide, in the allergic mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of tissue eosinophil counts in histologic sections is a common approach to reporting tissue inflammation. Calculation of tissue eosinophils for statistical comparisons, however, carries a high inherent variability . Real‐time polymerase chain reaction (RT‐PCR), on the other hand, is a more quantitative method that may provide a consistent measure of tissue inflammation .…”
mentioning
confidence: 99%
“…More recently, Kim et al created a model for recalcitrant allergic CRS by challenging the mice with OVA and Aspergillus protease, which is known to trigger allergic reactions in mouse lungs . However, their original model using OVA and SEB has allowed many great discoveries about the pathophysiology of CRS . In some transgenic strains of mice, small modifications to the concentration, dose, and frequency are required to induce inflammation and nasal polyposis.…”
Section: Introductionmentioning
confidence: 99%